Blood promise - Mead, Richelle (London : Penguin Books, 2013)
Just days before graduating from St. Vladimir's Academy, guardian-in-training Rose travels to Siberia to drive a stake into the heart of the boy she loves, the monstrous vampire Dimitri.
Young Adult.
Young Adult
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Supernatural -- Juvenile fiction; Vampires -- Juvenile fiction; High schools -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Vampires -- Fiction; High schools -- Fiction; School stories; Supernatural -- Fiction; Vampires -- Fiction; Russia (Federation) -- Juvenile fiction; Siberia (Russia) -- Juvenile fiction; Russia (Federation) -- Fiction; Siberia (Russia) -- Fiction; Russia -- Fiction; Siberia (Russia) -- Fiction